The Uptake Mechanism of the Cell-Penetrating pVEC Peptide - Ihsan Omur Akdag; Elif Ozkirimli (Journal of Chemistry)
Peptide based drug design efforts have gained renewed interest with the discovery of cargo-carrying or cell-penetrating peptides. Understanding the translocation mechanism of these peptides and identifying the residues or elements that contribute to uptake can provide valuable clues toward the design of novel peptides. To this end, we have performed steered molecular dynamics (SMD) simulations on the pVEC peptide from murine vascular endothelial-cadherin protein and its two variants. Translocation was found to occur in three stages, adsorption via the cationic residues, inclusion of the whole peptide inside the membrane accompanied by formation of a water defect, and exit of both peptide and water molecules from the bilayer. Our simulation results suggest that the precise order in which the hydrophobic, cationic, and the polar regions are located in the amphipathic pVEC peptide contributes to its uptake mechanism. These results present new opportunities for the design of novel cell-penetrating and antimicrobial peptides.